Developing a methodology to create nutritionally balanced meals. Issue 6 (4th February 2021) - Giazitzi, Katerina; Boskou, George
Abstract : Purpose: The purpose of the present study was to develop a methodology for the creation of nutritionally balanced (NB) recipes and meals. Design/methodology/approach: Nutritional criteria were set for energy, fats, saturated fats, carbohydrates, sugars and salt. A sample of 50 main courses and 29 salads was evaluated and nutritionally reformulated to meet the criteria. One sample t -test, paired sample t -test, Pearson correlation coefficient and linear regression analysis were performed. Findings: The original main courses and salads did not meet the nutritional criteria for fats and energy. Both original and NB main courses had high mean protein content. The reformulation of recipes caused a significant change on the provided energy (−50.2%), fats (−57.6%), saturated fats (−58.8%), carbohydrates (−24.2%), proteins (−35.6%) and salt (−53.8%) for the salads ( p = 0.001). Accordingly, reformulation of recipes caused a significant change on provided energy (−38.4%), fats (−55.2%), saturated fats (−58.3%), proteins (−25.9%) and salt (−50%) for the main courses ( p < 0.001). Predictive models (linear regression analysis) for fats ( R 2 = 0.345), proteins ( R 2 = 0.876) and carbohydrates ( R 2 = 0.797) on the NB recipes were performed. Originality/value: This is the first attempt to improve the nutritional value of cooking recipes, based on specific nutritional criteria. A methodological procedure for the creation of NB meals is proposed. This methodology could be a useful tool for the nutritionists and chefs, which, in a context of cooperation, could create databases and cooking books with NB recipes easily accessed to public and caterers. The recipes that constitute NB meals could guarantee the standardization of the recipes' reformulation, within a certification standard for restaurants.